Perencanaan Pengembangan Industri Genteng dengan Metode Analytical Hierarchy Process dan Linear Goal Programming - Purwatiningsih, Dyah Retno (Jurnal Teknik Industri, 2008)
CV Lestari Jaya is an enterprise that produce roof – tile, There are some Production centrals of roof – tile in Malang, One of them is CV Lestari Jaya. CV Lestari Jaya located in dukuh Wendit Pakis Malang. In applying this planning, CV Lestari Jaya must compete with after enterprises or factories. CV Lestari Jaya have to maintain costumers, and also anticipate market need which always increase. Knowing this condition, the writer will give an alternative to solve this problem with identification and analyze the condition of enterprise, not only internal and external condition but also the profit, of enterprise competitive by using Analytical Hierarchy Process (AHP) and Linear Goal Programming (LGP) Method. In this thasis Analytical Hierarchy Process (AHP) method was used because by using this method the out come of priority calculation indicate of roof – tile which wanted by costumers than other products CV Lestari Jaya that produce genteng super wendit will try to increase the quality of their product. Linear Goal Programming (LGP) Method was also used in by using QS (Quantitative System) program was obtained the stategy of planning of developing roof-tile Industry based on priority consecutively, then emphasizing the analysis was calculating the quantity of roof-tile product to find the better one. So, the purposes reached whit optimun valve it also anticipate the need market and maximize the enterprise/factory profit, too.